The impact of product market competition on firm performance through the mediating of corporate governance index: empirical of listed companies in Vietnam - Thach Xuan Ha; Thu Thi Tran (Cogent Business & Management, 2022)
Over the past decade, Vietnam has opened the market and attended in large economic organization like ASEAN Free Trade Area, ASEAN Comprehensive Investment Agreement, Regional Comprehensive Economic Partnership, Comprehensive and Progressive Agreement for Trans-Pacific Partnership. Therefore, the increasing of product market competition has a significant impact on businesses. In order for businesses to improve firm performance, the solution needed today is to improve corporate governance system. Corporate governance not only helps to limit agency problem but also increases the role of inspection, control, and orientation for the development of business activities. The study examines the influence of product market competition on firm performance through the mediating role of corporate governance. Our data collected from Thomson—Reuters DataStream and finance report of 180 listed non—finance companies in Vietnam from 2015 to 2019. The research model and hypotheses were tested by Maximum Likelihood with Structural Equation Model method in Stata 14 software. The results showed that product market competition has positive effect firm performance through the mediating of corporate governance. Besides, the study revealed that business strategy negatively and significantly effects on product market competition and firm performance. Research results provide theoretical and administrative implications for improving firm performance.